The discovery of pancreatic diabetes: the role of Oscar Minkowski - Houssay, Bernardo A. (1952)
In 1889 von Mering and Minkowski reported that total pancreatectomy in dogs was followed by severe diabetes. This was a discovery of historic importance. It demonstrated that diabetes occurs in the absence of the pancreas; and this finding furnished the starting point for research which proved that this organ produces an internal secretion, thus leading to the discovery of insulin and its application to the treatment of patients suffering from diabetes. Studies on carbohydrate metabolism were considerably extended, and it became possible to demonstrate the role of the liver in this metabolism and the regulatory functions of hormones secreted by several endocrine glands in normal conditions and in diabetes.